PERFORMANCE GURU DALAM DISIPLIN BELAJAR SISWA DI SMPN 24 KOTA JAMBI - Debora Audri Panjaitan; Sofyan Sofyan; Erisa Kurniati (STKIP Pesisir Selatan, 2026)
This study aims to analyze teacher performance in shaping students’ learning discipline at SMP Negeri 24 Kota Jambi. This research uses a qualitative approach with a case study design to gain an in-depth understanding of teacher performance in real classroom contexts. Data were collected through participatory observation, semi-structured interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The results show that teacher performance in the learning process is categorized as good to very good, as reflected in lesson planning, mastery of subject matter, use of teaching methods, classroom management, and evaluation practices. Students’ learning discipline is generally classified as quite good; however, it has not been evenly distributed, as some students still show low focus, lack of participation, and inconsistency in completing assignments. Teacher performance plays a significant role in shaping students’ discipline through the creation of engaging, interactive, and conducive learning environments, as well as through motivation, guidance, reinforcement, and classroom control. The novelty of this study lies in its emphasis on how teacher performance directly influences students’ learning discipline in a contextual classroom setting, highlighting that discipline is not solely formed by rules but is strongly shaped by the quality of teaching practices.